La restructuration récente des politiques sociales au Canada et au Québec: éléments d’analyse - Groulx, Lionel-Henri (Labour / Le Travail, 2009)
Abstract Since the mid-1990’s, Canada and Quebec have initiated important changes to their system of social protection; the objectives of the reforms were to control public expenditure or attain zero deficit, improve the efficiency of social policies, particularly in relation to employment incentives, and guarantee acceptable living conditions. Such objectives were conveyed by a restructuring of several social protection mechanisms, achieved by reconfiguring protection parameters and activating the same social expenditure. To understand this restructuring, the article analyses the changes introduced in certain income security mechanisms including unemployment insurance, universal family allowance and welfare, at both the Federal and Quebec levels. To explain this approach, the paper is divided into three parts: the first on the reconfiguration of each mechanism, the second on the activation of social expenditure and the third introducing the elements of analysis towards this recent restructuring of social policies. The subject matter is dominated by a fundamental question, that of knowing whether the reforms convey a neo-liberal change of policy in the disengagement of the state and erosion of social rights or whether they convey a reorganization, a modification of the framework as a result of change of paradigm or reference in a socially active state or as a form of social investment.